2016
DOI: 10.4103/2278-9626.189252
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of dental anxiety among adult population in Benin City, Nigeria

Abstract: Objectives: Dental anxiety is a significant determinant of regular dental visits. The objectives of the study were to determine the prevalence and determinants of dental anxiety among adult patients at the dental center of the University of Benin Teaching Hospital. Subjects and Methods: A total of 390 respondents aged 16-89-year-old were interviewed for the study. The Participants were selected through a predetermined sequence of systematic random sampling and completed a questionnaire based on the Coral Denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 20 publications
(40 reference statements)
3
26
1
Order By: Relevance
“…Contrary to the findings in the literature [ 1 , 21 ], in this study, it was found that participants with a higher level of education were more anxious than those with lower education levels. Our findings were similar to the findings from elsewhere [ 8 , 27 , 29 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to the findings in the literature [ 1 , 21 ], in this study, it was found that participants with a higher level of education were more anxious than those with lower education levels. Our findings were similar to the findings from elsewhere [ 8 , 27 , 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have suggested that dental anxiety is lower in the older age groups [3,21,27,28], and results from this study have similar findings. Young patients were 3 times more anxious than the older ones.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations